the PLANT CLINIC : Healing with plant medicine - Verinder, Erin Lovell; Blackie, Georgia (Port Melbourne, Victoria : Thomas & Hudson Australia, 2021)
The Plant Clinic is a revolutionary new guide to reignite your health and transform your life. Expert herbalist Erin Lovell Verinder decodes healing with plant medicine to remedy over 150 common health complaints across: Vitality; Immunity; Detoxification; The Gut; Hormone Health; Mums and Bubs; Hair and Skin; Emotions, Mind and Spirit. Nettle and Oat Straw Infusion is essential to bring people back from burnout; Liver Loving Greens Powder is a wonder for detox support; Iron Lift Slow Brew Syrup is for everyone with low iron levels; and the Lovers' Oxymel is delicious, helpful and so different from other libido support. With over 150 recipes, including Lung Love Syrup, Zen Day Tea, The Breakout Salve, Eczema Cream, Kidney Tone Tea and Shifting Stagnancy Tea, this book is the definitive healing bible for modern day living. Sharing deep herbal wisdom along with the ultimate First Aid Kit for soothing bruises, aches and pains and much, much more, this is the book to make you glow.
Includes index.
Keywords: Alternative medicine; Medicine, Botanic; Medicinal plants; Materia medica, Vegetable; Herbs -- Therapeutic use; Herbals